Barroso Cabrera, R.; Morín de Pablos, J. e I. Mª Sánchez Ramos (2018): Thevdemirvs dux. El último godo. El ducado de Aurariola y el final del reino visigodo de Toledo. Serie Histórica. Madrid: Audema. 216 págs. ISBN: 978-84-16450-38-1. - Castillo Lozano, José Ángel (Antigüedad y Cristianismo, 2019)
Recensión